2006
DOI: 10.1055/s-2006-944287
|View full text |Cite
|
Sign up to set email alerts
|

Spontan rupturiertes Angiomyolipom der Nebenniere

Abstract: Retroperitoneal haemorrhages mostly occur as a result of trauma. Besides a traumatic origin of retroperitoneal haemorrhage, the other most common cause is an anticoagulation therapy. Further potential sources of retroperitoneal hematoma are benign and malignant tumours of the adrenal gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A review of the literature revealed 17 previously reported cases of adrenal angiomyolipoma. Of these, 14 were sporadic and 3 were reported in patients with tuberous sclerosis or lymphangioleiomyomatosis [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. There was 1 reported case of spontaneous haemorrhage [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature revealed 17 previously reported cases of adrenal angiomyolipoma. Of these, 14 were sporadic and 3 were reported in patients with tuberous sclerosis or lymphangioleiomyomatosis [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. There was 1 reported case of spontaneous haemorrhage [4].…”
Section: Discussionmentioning
confidence: 99%
“…They are benign endocrinologically inactive tumours with a histological structure consisting of variable amounts of adipose, thick-walled blood vessels and smooth muscle cells [1]. Commonly, angiomyolipomas occur in the kidney with few extra renal case reports in adrenals, bone, breast, colon, heart, liver, lung, parotid gland, retroperitoneum, skin and spermatic cord [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical management has been proposed for lesions >5cm, even if non-functional, to avoid complications of free spontaneous rupture as some such cases in patients on anticoagulants have been reported, for example by Stolle et al 15 The surgical technique for removal of angiomyolipomas can be open or laparoscopic. With recent advances in the laparoscopic technique, even large angiomyolipomas have been removed with a flank-based transperitoneal laparoscopic approach, 16 17 indicating a gradual progression towards being less dependent on tumour size before deciding on one particular technique.…”
Section: Managementmentioning
confidence: 99%